2018
DOI: 10.1177/1071100718757971
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Percutaneous Fixation of Acute Achilles Tendon Ruptures

Abstract: Level II, prospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 21 publications
(26 reference statements)
2
38
0
Order By: Relevance
“…In patients with Achilles tendon rupture, bundle-to-bundle suturing is the most effective surgical method to restore the anatomical structure and physiological characteristics of the tendon [ 4 6 ]. Open repair enables direct repair of the rupture site and achievement of maximum mechanical stability [ 4 7 , 22 ]; however, the complex sutures used in the modified Bunnell suture technique can form a fiber block of the Achilles tendon that may result in keloid formation and tendon shortening [ 7 , 12 , 23 26 ]. Open repair also reportedly causes scar contracture of the Achilles tendon [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with Achilles tendon rupture, bundle-to-bundle suturing is the most effective surgical method to restore the anatomical structure and physiological characteristics of the tendon [ 4 6 ]. Open repair enables direct repair of the rupture site and achievement of maximum mechanical stability [ 4 7 , 22 ]; however, the complex sutures used in the modified Bunnell suture technique can form a fiber block of the Achilles tendon that may result in keloid formation and tendon shortening [ 7 , 12 , 23 26 ]. Open repair also reportedly causes scar contracture of the Achilles tendon [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This technique of endoscopically assisted repair is not novel to our series and has been reported in previous studies with favorable results. 3,10,30,31 Halasi et al 11 reported a large series of percutaneous repairs with and without endoscopic control and had fewer reruptures in the endoscopic group, thus concluding that this technique allows for a more thorough evaluation of tendon apposition after repair. 10 Though reasonable, we do not routinely do this with our technique.…”
Section: Discussionmentioning
confidence: 99%
“…32 Although there were favorable results of percutaneous Achilles repairs in the literature with lower wound complications compared with open approaches, there were concerns of tendon rerupture (8%) from not being able to directly visualize the Achilles repair and sural nerve injury (13%). 12,26,48 In 1995, Kakiuchi and colleagues adapted their percutaneous repair by adding a mini-open incision to place their twisted K-wire suture guide. 23 Majewski and colleagues described using a 1.5-cm accessory lateral incision at the level of the Achilles rupture to retract the subcutaneous tissues and sural nerve.…”
Section: Discussionmentioning
confidence: 99%